Desa dalam Administrasi Publik Indonesia Kontemporer: Penguatan Peran LAN - Nurjaman, Rusman; Prasetyo, Antonius Galih (Jurnal Borneo Administrator, 2018)
Law No. 6 of 2014 on Villages provides a momentum and wide opportunities to make the village as the subject of development as well as placing it as a new axis of the national development based on the principle of participation, accountability, mutual cooperation, empowerment, sustainability, local wisdom, and independence. In another context, this Law also provides a new perspective on public administration in Indonesia. Affirmation of the principle of recognition and subsidiarity puts villages outside the hierarchial framework of the government. Unfortunately, this reality is often not considered by the national and local government with the right policies and approaches. National Institute of Public Administration (NIPA) responds to this situation by conducting a number of relevant researches. Following the ratification of Law on Villages, LAN has conducted a series of studies on villages that resulted in interesting findings that can be used to reflect the village position in the contemporary public administration order. There are three clusters of public administration issues that can be drawn from those researches, among them are the relationship between village and supravillage government, village authority, and the capacity of village governemnt. In the future, it is expected that LAN continues to play a role in developing village. Not only through research activities, but also through public administration innovation, apparatus training, and higher education of administration. Keyword: Village, public administration, NIPA, think tank, recognition, subsidiarity Abstrak UU No. 6 Tahun 2014 tentang Desa memberikan momentum dan peluang yang lebar untuk menjadikan desa sebagai subjek pembangunan sekaligus menempatkannya sebagai poros baru pembangunan nasional yang bertumpu pada prinsip partisipasi, akuntabilitas, kegotongroyongan, pemberdayaan, keberlanjutan, kearifan lokal, dan kemandirian. Dalam konteks lain, UU ini juga memberikan perspektif baru mengenai administrasi negara di Indonesia. Penegasan asas rekognisi dan subsidiaritas desa menempatkan desa di luar kerangka hierarkial pemerintahan. Sayangnya, kenyataan ini kadang tidak disadari oleh pemerintah dan daerah melalui kebijakan dan pendekatan yang tepat. Lembaga Administrasi Negara (LAN) merespons hal ini dengan melaksanakan sejumlah kajian terkait. Pasca pengesahan UU Desa, LAN telah menyelenggarakan kajian mengenai desa dengan berbagai temuan menarik yang dapat dipakai untuk merefleksikan posisi desa dalam tatanan administrasi negara kontemporer. Ada tiga klaster isu administrasi negara yang dapat ditarik dari berbagai kajian tersebut, di antaranya hubungan desa dengan pemerintah supradesa, kewenangan desa, dan kapasitas pemerintah desa. Di masa depan, diharapkan LAN terus berperan dalam memajukan desa. Tidak saja melalui kegiatan kajian, namun juga melalui inovasi administrasi negara, diklat aparatur, dan pendidikan tinggi administrasi. Kata Kunci: Desa, administrasi negara, LAN, think tank, rekognisi, subsidiaritas